Determinan Kesiapan Ibu Hamil yang Bekerja Diluar Rumah dalam Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Mesjid Raya Kabupaten Aceh Besar - Cut Oktaviyana; Syarifah Masthura; Rizka Akmalia (Universitas Maritim AMNI Semarang, 2025)
The nursing process must be adequately prepared for throughout pregnancy to ensure its flawless execution. Preparation for breastfeeding should commence during pregnancy, particularly for working moms who are unable to produce direct breast milk and are away from home for several hours daily. The study aimed to examine the factors influencing the preparedness of employed pregnant women to provide exclusive breastfeeding under the jurisdiction of the Krueng Raya Health Center, Mesjid Raya District, Aceh Besar Regency. Employing a quantitative research methodology utilizing an observational analytical survey via a cross-sectional technique. The study population comprised 42 pregnant women employed outside the house. The employed sample technique was complete sampling. The study's findings indicated a correlation between breast milk pumping equipment and the preparedness of employed pregnant women for exclusive breastfeeding (p = 0.047), knowledge and the preparedness of employed pregnant women for exclusive breastfeeding (p = 0.047), attitude and the preparedness of employed pregnant women for exclusive breastfeeding (p = 0.001), and spousal support and the preparedness of employed pregnant women for exclusive breastfeeding (p = 0.003). Nonetheless, there exists no correlation between the accessibility of facilities and the preparedness of employed pregnant women to provide exclusive breastfeeding (p = 0.058). The enhancement of breastfeeding preparation for pregnant women is essential to ensure the effective implementation of exclusive breastfeeding post-delivery.